2016
DOI: 10.1016/j.jhazmat.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

The impact on the soil microbial community and enzyme activity of two earthworm species during the bioremediation of pentachlorophenol-contaminated soils

Abstract: The ecological effect of earthworms on the fate of soil pentachlorophenol (PCP) differs with species. This study addressed the roles and mechanisms by which two earthworm species (epigeic Eisenia fetida and endogeic Amynthas robustus E. Perrier) affect the soil microbial community and enzyme activity during the bioremediation of PCP-contaminated soils. A. robustus removed more soil PCP than did E. foetida. A. robustus improved nitrogen utilisation efficiency and soil oxidation more than did E. foetida, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 54 publications
2
22
0
1
Order By: Relevance
“…between microorganisms and reactants (Lin et al, 2016b). Additionally, earthworms also increase soil microbial activities via digesting organic matters and improving nutrient availability (Lin et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…between microorganisms and reactants (Lin et al, 2016b). Additionally, earthworms also increase soil microbial activities via digesting organic matters and improving nutrient availability (Lin et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the biochemical treatment units in WWTPs are sensitive to high-level of toxic emerging substances or PTEs in influents and the paralysis often occurs in case of a shock load. It is reported that the spill of cyanide and other illegal chemical dumping can cause the shutdown of WWTPs and consequently release contaminants to the surrounding environment [14]. Toxicity assessment methods require development for monitoring the change of influent toxicity and guiding the rapid response strategies to protect WWTPs from the shock load [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most of these approaches are still in laboratory test, leaving a huge gap between the state-of-art concept and industrial practices. Besides, these biological measurements are indirect methods as the indicator organisms are exogenous to the activated sludge and unable to represent the real domestication and adaptability of the activated sludge during wastewater treatment process [14]. An early-warning system directly monitoring the change of the activated sludge activities can represent the real performance of WWTPs and provide a basis for emergency measures of toxic substances in industrial wastewater, for effectively evaluating the influent toxicity and alarming the shock load of industrial wastewater [3,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La implementación de lombrices para la biorremediación es una técnica novedosa que ha mostrado que las capacidades de asimilación de metales por vía digestiva es prácticamente independiente del pH del suelo [27]. A través de las secreciones mucilaginosas y la transformación de materia orgánica, las lombrices incrementan la actividad microbial y la disponibilidad de los nutrientes, de igual manera se ha reportado que las lombrices pueden estimular las bacterias, hongos y especies relacionadas con la degradación del pentaclorofenol [28][29][30][31][32].…”
Section: Introductionunclassified